2019
DOI: 10.1002/ptr.6553
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxycinnamic acid suppresses airway inflammation and mucus hypersecretion in allergic asthma induced by ovalbumin challenge

Abstract: In this study, we investigated whether 4‐hydroxycinnamic acid (HA) has a palliative effect on asthmatic inflammatory responses using a mouse model of ovalbumin (OVA)‐induced allergic asthma. The mice were divided into five groups, each consisting of seven females (normal control phosphate‐buffered saline); OVA (OVA sensitization/challenge); dexamethasone (DEX, OVA sensitization/challenge + dexamethasone 3 mg/kg); HA‐10 and HA‐20 OVA sensitization/challenge + HA 10 and 20 mg/kg, respectively). Mice treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The decreased abundance of these three metabolites in the stress-induced IBS rat model indicates that colonic immune instability might be affected. The increased metabolic of dl -3-Phenyllactic acid 60 and 4-Hydroxycinnamic acid 61 , 62 , which has many pharmacological properties including immune-modulatory, anti-inflammatory and antioxidant effects, may be involved in regulating the imbalance of intestinal immunity. These two isoforms of Phenylalanine, l .Phenylalanine and dl .Phenylalanine have similar physiological efficacy, and these were detected to be highly produced in the stress-induced model, indicating the low bioavailability of metabolites in the intestine of stress rats.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased abundance of these three metabolites in the stress-induced IBS rat model indicates that colonic immune instability might be affected. The increased metabolic of dl -3-Phenyllactic acid 60 and 4-Hydroxycinnamic acid 61 , 62 , which has many pharmacological properties including immune-modulatory, anti-inflammatory and antioxidant effects, may be involved in regulating the imbalance of intestinal immunity. These two isoforms of Phenylalanine, l .Phenylalanine and dl .Phenylalanine have similar physiological efficacy, and these were detected to be highly produced in the stress-induced model, indicating the low bioavailability of metabolites in the intestine of stress rats.…”
Section: Discussionmentioning
confidence: 99%
“…), and CIE L or H (OVA treatment + CIE 100 or 300 mg/kg, p.o., respectively). The allergic asthma mouse model was induced through OVA using the method described in our previous study [ 18 ]. Briefly, each mouse was immunized by 20 μg OVA (emulsified in 10 mg/mL of aluminum hydroxide and PBS) intraperitoneal injection on test days 0 and 14.…”
Section: Methodsmentioning
confidence: 99%
“…As described in the previous paper, MMP-9 activity was measured by the gelatin zymography test method [ 18 ]. In principle, blue-stained gel is visualized as a white band by dissolving gelatin where MMP-9 activity is high.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that HA is increased in both bronchioalveolar fluid ( Bousquet et al, 1991 ; Zhu et al, 2010 ; Ge et al, 2018 ) and in ECM produced when HBECs of asthmatics are cultured with human lung fibroblasts ( Reeves et al, 2018 ). Its ability to suppress airway inflammation and mucus secretion, indicating that HA may be a potential therapeutic option for reducing remodeling in asthma ( Ko et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies may be attributed to the severity of the disease or localization of specific MMP responses ( Araujo et al, 2008 ), significant research still needs to be carried out in this area and likely requires the use of more complex, human tissue-level studies comprising of all the cells in an EMTU. MMP-9 and MMP-12 are increased in the airway smooth muscle of the large airways in fatal cases of asthma ( Araujo et al, 2008 ) and it has been shown that HA may play a role in suppressing MMP9 production and be of potential therapeutic benefit ( Ko et al, 2020 ). More recently a role for MMP2, expressed by HBECs, has been considered in ECM remodeling and data suggests that MMP2 may be key in mediating crosstalk between HBEC and their underlying myofibroblasts in the EMTU and that a net change in MMP2 activity in asthma may promote fibrosis and increased deposition of ECM, despite its role in ECM degradation ( Xu et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%